2011
DOI: 10.1128/aem.05498-11
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Bacteria in Outdoor Air across Cities in the Midwestern United States

Abstract: Bacteria are abundant in the atmosphere, where they often represent a major portion of the organic aerosols. Potential pathogens of plants and livestock are commonly dispersed through the atmosphere, and airborne bacteria can have important effects on human health as pathogens or triggers of allergic asthma and seasonal allergies. Despite their importance, the diversity and biogeography of airborne microorganisms remain poorly understood. We used high-throughput pyrosequencing to analyze bacterial communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
207
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(248 citation statements)
references
References 43 publications
28
207
5
1
Order By: Relevance
“…It is also reasonable to hypothesize that different bacterial species show different CCN/IN efficiencies and, thus, at high altitudes, we have preferentially sampled species that are not as efficient CCN/IN; i.e., they are less affected by wet scavenging at lower altitudes. Consistent with this hypothesis, we found that Gammaproteobacteria, the most efficient IN bacteria known, did not make up a proportionally large part of the tropospheric communities (SI Appendix, Table S3) compared with the near-surface communities studied previously (9,11,12). Furthermore, model simulations have shown that CCN-active microorganisms have a shorter residence time in the atmosphere than those that are CCN-inactive (29).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…It is also reasonable to hypothesize that different bacterial species show different CCN/IN efficiencies and, thus, at high altitudes, we have preferentially sampled species that are not as efficient CCN/IN; i.e., they are less affected by wet scavenging at lower altitudes. Consistent with this hypothesis, we found that Gammaproteobacteria, the most efficient IN bacteria known, did not make up a proportionally large part of the tropospheric communities (SI Appendix, Table S3) compared with the near-surface communities studied previously (9,11,12). Furthermore, model simulations have shown that CCN-active microorganisms have a shorter residence time in the atmosphere than those that are CCN-inactive (29).…”
Section: Discussionsupporting
confidence: 71%
“…For example, substantially fewer OTUs were found in this study compared with samples collected at 3.2 km at the top of Colorado mountains (9), indicating that not all microbial cells can apparently reach or survive highaltitude conditions. Furthermore, contrary to previous surveys of near-surface atmospheric samples (9,11,12), Gammaproteobacteria did not make up a proportionally large part of the tropospheric communities sampled. These findings might reflect the influence of atmospheric processes and transport of the bacterial cells because several members of Gammaproteobacteria, for example, are known to be CCN-and IN-active.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The presence of viable Bacteroidetes (15.8%) in buckets/drums (Fig 3) is also an indication of soil (dust) contamination as Bacteroidetes originating from leaf surfaces, soil and animal fecal matter sources are present in near-surface atmospheric particulate matter (Bowers et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Taxa that dominate the total bacterial community may represent groups that become entrained in the atmosphere (Morris et al 2008, Bowers et al 2011) and redistributed over broad scales. While the near-ground aeolian redistribution of cyanobacteria has been documented in the Dry Valleys (Wood et al 2008, Michaud et al 2012, cyanobacteria appear to be a minor component in more broadly dispersed bioaerosols (Bottos et al 2013).…”
Section: Local and Regional Influences Over Antarctic Microbial Metacmentioning
confidence: 99%